Genomic Characteristics of Colistin-Resistant Salmonella enterica subsp. enterica Serovar Infantis from Poultry Farms in the Republic of Serbia - Branko Jovčić; Katarina Novović; Brankica Filipić; Maja Velhner; Dalibor Todorović; Kazimir Matović; Zoran Rašić; Sonja Nikolić; Ferenc Kiškarolj; Milan Kojić (MDPI AG, 2020)
The antimicrobial susceptibility testing was conducted on 174 single isolates from poultry farms in Serbia and it was determined that seven Salmonella spp. were multidrug resistant. Sixteen serotypes were detected, but only serotype Infantis confirmed reduced susceptibility to colistin. Seven colistin resistant Salmonella Infantis were studied in detail using the WGS approach. Three sequence types were identified corresponding to different epizootiology region. The isolate from the Province of Vojvodina 3842 and isolates from Jagodina (92 and 821) are represented by the sequence type ST413 and ST11, respectively. Four isolates from Kraljevo are ST32, a common S. Infantis sequence type in humans, poultry and food. The fosfomycin resistance gene fosA7 in isolate 3842 and the vgaA gene in isolate 8418/2948 encoding resistance to pleuromutilins were reported for the first time in serovar Infantis. The changes in relative expression of the phoP/Q, mgrB and pmrA/B genes were detected. Single nucleotide polymorphisms of the pmrB gene, including transitions Val164Gly or Val164Met, and Arg92Pro are described. Analyses of quinolone resistance determining region revealed substitutions Ser83Tyr in GyrA protein and Thr57Ser and Ser80Arg in ParC protein. Based on WGS data, there are two major clusters among analyzed Salmonella Infantis isolates from central Serbia.